Plan de recuperación de cartera vencida y solvencia de microcréditos en BanEcuador sucursal Babahoyo. - Gavica Roelas, Josué Luciano (2024)
This research focuses on the management of the microcredit portfolio at BanEcuador, Babahoyo Branch, addressing the growing problem of overdue loans and the solvency of microcredits. The past due portfolio has generated a significant increase in delinquency rates, affecting the bank's financial stability and compromising its ability to provide sustainable credit services. The general objective is to develop an efficient recovery plan to reduce overdue loans immediately. The methodology involves inductive and analytical methods, applying the sample size formula for finite populations. The results focus on specific strategies for the identification and recovery of overdue loans, improving the solvency of microcredits. The importance of research in the field of Financial Management and related areas such as administrative, tax, auditing and control is highlighted. The conclusions highlight the viability and relevance of the proposed plan to improve the management of the microcredit portfolio, benefiting both the bank and the users. Keywords: past due portfolio, microcredits, financial management, recovery strategies, BanEcuador.